2021
DOI: 10.1177/15347346211009409
|View full text |Cite
|
Sign up to set email alerts
|

Onychomycosis and Tinea Pedis in the Feet of Patients With Diabetes

Abstract: This study aimed to determine the prevalence of onychomycosis and interdigital tinea pedis in a cohort of Spanish patients with diabetes in whom onychomycosis was clinically suspected (n = 101). Samples from a first toenail scraping and the fourth toe clefts were subjected to potassium hydroxide direct vision and incubated in Sabouraud and dermatophyte test medium. Fifty-eight samples were also analyzed by a pathologist using periodic acid-Schiff staining and Calcofluor white direct fluorescence microscopy. On… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
1
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(36 citation statements)
references
References 35 publications
0
30
1
5
Order By: Relevance
“…T. interdigitale was more common than T. rubrum in dermatophytic onychomycosis. Previous studies carried out in urban areas of Spain revealed that dermatophytes and T. rubrum were the most common etiological agents of onychomycosis [16,20,21]. We believe that the discrepancies between our findings and those others are due to different lifestyles, rural vs. urban.…”
Section: Discussioncontrasting
confidence: 82%
“…T. interdigitale was more common than T. rubrum in dermatophytic onychomycosis. Previous studies carried out in urban areas of Spain revealed that dermatophytes and T. rubrum were the most common etiological agents of onychomycosis [16,20,21]. We believe that the discrepancies between our findings and those others are due to different lifestyles, rural vs. urban.…”
Section: Discussioncontrasting
confidence: 82%
“…With regard to clinical presentation, TDO and MO are the most common among the housed population and among the homeless population DSO and MO. Notwithstanding that fact, we have not found any recent studies that match the clinical presentations of our research since most studies describe that the most frequent clinical presentation is DLSO [ 6 , 21 , 22 ]. This could be explained by our sample size.…”
Section: Discussionmentioning
confidence: 54%
“…Regarding the housed group, this prevalence is 62.5%, which enhances the results obtained by Babayani, M. et al, in their study published in 2018 which found prevalence was 65.5% ( n = 118) [ 20 ]. Aragón-Sánchez, J. et al, in their study published in 2021 using similar techniques as those used in this study, obtained diagnoses confirmation in 40.5% of the cases with clinical suspicion ( n = 101) [ 21 ]. However, this comparison should be taken cautiously since their target population was only diabetic.…”
Section: Discussionmentioning
confidence: 94%
“…Chronic hyperglycaemia, neuropathy and peripheral arterial disease damage the immune system by affecting polymorphonuclear leukocytes and phagocytic functions. These conditions are present in diabetic foot patients and contribute to the development of fungal and bacterial skin infections as well as fungal nail infections 7,8 …”
Section: Introductionmentioning
confidence: 99%